(untitled) (Intelligere, 2023)
International Relations as a field of study was introduced to Brazilianuniversities by the University of Brasilia in 1974. This essay presents and analyzes of such an experience of establishing a new academic field of studies in Brazilian universities and in the intellectual environment of a country which was going through remarkable economic, political, and social changes.